Applying quality by design to glycoprotein therapeutics: experimental and computational efforts of process control - Jedrzejewski,PM; Jimenez,del Val I; Polizzi,KM; Kontoravdi,C (Pharmaceutical Bioprocessing, 2013)
Therapeutic glycoproteins represent one of the most important classes of products in the pharmaceutical industry, accounting for 77 high-value drugs out of 642 pharmaceuticals approved by the European Medicines Agency. Their therapeutic efficacy, serum half-life and immunogenicity depend on glycosylation, a complex and prominent post-translational event, which in turn is influenced by manufacturing process conditions. For this reason, protein glycosylation is a critical quality attribute for these drugs. Herein, we review the impact of glycosylation on product function, and the role of manufacturing conditions on the resulting glycoform distribution. We further present promising developments in terms of alternative, genetically engineered hosts, as well as advances in process operation that influence the glycan profile of the recombinant product. Finally, we review work on dynamic mathematical modeling for protein glycosylation that allows researchers to evaluate genetic engineering and process operation strategies in silico, with the aim of guiding experimentation. We demonstrate that such model-based approaches, when substantiated by experimental evidence, can support the quality by design initiative and expedite process development.